The impact of CBDC on a deposit-dependent banking system - Vollmar, Steffen; Wening, Fabian (Journal of Financial Stability, 2024)
We examine implications of a central bank digital currency (CBDC) for banks using business models particularly dependent on customer deposits. Employing unique customer data hand-collected from German savings and cooperative banks, we generate conversion rates for deposits into a CBDC. Even at moderate conversion rates, most banks would have experienced funding problems and lost profits if a CBDC had been introduced in most years from 2000 onward. Our results are relevant for commercial banks, contributing to better assessments of the impact of CBDCs on liquidity and profitability and help central banks to identify implementation costs for banks within historical and hypothetical interest rate environments.